Targeting the liver serine protease TMPRSS6 ameliorates steatosis and attenuates fibrosis in experimental MASLD - Pettinato, Mariateresa; Furiosi, Valeria; Carleo, Rossana; Bavuso Volpe, Letizia; Guo, Shuling; Mannella, Valeria; Musco, Giovanna; Gilberti, Enrica; De Palma, Giuseppe; Federico, Giorgia; Carlomagno, Francesca; Cherubini, Alessandro; et al. (Liver international, 2025)
Background and Aims Metabolic dysfunction-associated steatotic liver disease (MASLD) is the most common cause of liver disease and a leading contributor to liver-related morbidity and mortality. Currently, no pharmacological approach has demonstrated consistent and long-lasting benefits across all patients. Therefore, identifying new therapeutic targets remains an urgent clinical need. The hepatic serine protease matriptase-2, encoded by TMPRSS6, inhibits the BMP-SMAD pathway. Interestingly, reduced BMP-SMAD signalling in the liver is frequently associated with altered lipid metabolism in patients. Conversely, inactivation of Tmprss6 has been linked to reduced high-fat diet-induced obesity. Based on these findings, we hypothesize that TMPRSS6 represents a novel and promising target for the treatment of MASLD. Methods Hepatic TMPRSS6 expression was analysed in obese patients with or without MASLD. Adult male mice were fed a MASLD-MASH diet, and once hepatosteatosis was established, they were treated with antisense oligonucleotides targeting Tmprss6 while continuing the dietary regimen for an additional 6 weeks. Results The expression of the BMP-SMAD inhibitor TMPRSS6 was increased in people with MASLD and negatively correlated with PPARα signaling, a key regulator of hepatic lipid metabolism. In experimental MASLD, downregulation of hepatocytic Tmprss6 using GalNAc-ASO significantly reduced steatohepatitis and fibrosis and attenuated MASLD-MASH-associated ferroptosis by reshaping hepatic transcription factor activity towards PPARα and SMAD4/SMAD5-driven signalling. Consistently, enhanced BMP-SMAD signalling increased PPARα activity in vivo. Conclusions Our findings reveal a novel functional crosstalk between TMPRSS6 and PPARα. Pharmacological downregulation of Tmprss6 in experimental MASLD mitigates hepatosteatosis, inflammation and fibrosis by enhancing PPARα signalling and attenuating ferroptosis.
Zuerst veröffentlicht: 11. Juni 2025
Gesehen am 06.11.2025